The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.adolescence.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

School‐based early intervention for anxiety and depression in older adolescents: A feasibility randomised controlled trial of a self‐referral stress management workshop programme (“DISCOVER”)

Abstract: Daniel (2019) School-based early intervention for anxiety and depression in older adolescents: a feasibility randomised controlled trial of a self-referral stress management workshop programme ("DISCOVER").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 84 publications
4
24
0
3
Order By: Relevance
“…Participants engaged well with the goal review follow-up calls, with 73.3% of workshop attenders completing at least one call. This is similar to the rate of 78.8% reported in a previous evaluation of DISCOVER (Brown et al, 2019). In the qualitative feedback, participants described positive aspects of the calls, such as feeling acknowledged, but also advocated for alternative written communication methods in preference to telephone conversations.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Participants engaged well with the goal review follow-up calls, with 73.3% of workshop attenders completing at least one call. This is similar to the rate of 78.8% reported in a previous evaluation of DISCOVER (Brown et al, 2019). In the qualitative feedback, participants described positive aspects of the calls, such as feeling acknowledged, but also advocated for alternative written communication methods in preference to telephone conversations.…”
Section: Discussionsupporting
confidence: 84%
“…The present feasibility trial has demonstrated that a full-scale RCT of DISCOVER is warranted in specialist youth mental health clinics, building on existing studies of DISCOVER in self-referred community samples (Brown et al, 2019;Sclare et al, 2015). Our feasibility data point towards short-term improvements in participants' emotional functioning after participating in the DISCOVER workshop, along with an expressed need for additional therapeutic support to consolidate therapeutic gains.…”
Section: Recommendations For Future Researchmentioning
confidence: 67%
See 1 more Smart Citation
“…The project has led to improvements in the flourishing of over 1,000 secondary school-aged children in the region. The current study shows that the Hummingbird Project occupies a happy medium in the dichotomy between mental health professional-delivered, prescriptive interventions and the kind of interactive, self-management encouraging interventions that are preferred by older adolescents (Brown et al, 2019). As stated by one of the students that took part in the PPI, "The Hummingbird Project is amazing!…”
Section: Resultsmentioning
confidence: 75%
“…The current study is the qualitative component of a cluster randomised controlled trial (RCT) investigating the feasibility of the DISCOVER workshop programme for students in UK sixth forms (aged 16–19) in 10 Inner London schools, described in Brown et al. (). Schools were randomised into experimental and control groups.…”
Section: Introductionmentioning
confidence: 99%